THE INFLUENCE OF LEADERSHIP, WORKLOAD AND WORK ENVIRONMENT ON THE WORK MOTIVATION OF EMPLOYEES OF THE PERSONNEL AGENCY AND RESOURCE DEVELOPMENT HUMAN SOUTH COAST DISTRICT - Rahmadhani, Neneng; Susanti, Febsri (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the effect of leadership, workload and work environment on work motivation employees of Agency For Personnel and Human Resources Development Agency (BKPSDM) Pesisir Selatan Regency. The method used in this research is quantitative research with survey and descriptive approach. The population in this study were employees of Agency For Personnel and Human Resources Development Agency (BKPSDM) Pesisir Selatan Regency. The sample used was 48 people using saturated sampling technique. The data analysis technique is multiple linear regression. The results showed that: (1) Leadership has a positive and significant effect on work motivation employees, (2) Workload has a negative and significant effect on work motivation, (3) Work environment has a positive and significant effect on work motivation employees